SOCIAL JUSTICE ACCORDING TO JOHN RAWLS AND THE RESPONSIBILITY OF PASTORAL COUNSELORS FOR THE MARGINALIZED - Agrendi Mangali; Meilani Tundu; Joiske Takalamingan; Harjen Kahuweka (International Forum of Researchers and Lecturers, 2024)
This article entitled “Social Justice According to Jhon Rawls and the Pastoral Counselor’s Responsibility for the Marginalized” aims to describe the role of pastoral counseling in its responsibility to the marginalized using Jhon Rawls’ theory of social justice. This research uses literature research using descriptive analysis method. The data in this article is collected from various sources such as books and journals. And the result of this research is the importance of the church in caring for the marginalized and also the application of pastoral counseling within the church in order to assist the marginalized and apply the theory of social justice.